From the Peaks to the Valleys: Cross-State Evidence on Income Volatility over the Business Cycle - Carey, Colleen; Shore, Stephen H. (The Review of Economics and Statistics, 2013)
Countercyclical variation in individuals' idiosyncratic labor income risk could generate substantial welfare costs. Following past research, we infer income volatility—the variance of permanent income shocks, a standard proxy for income risk—from the rate at which cross-sectional variances of income rise over the life cycle for a given cohort. Our novelty lies in exploiting cross-state variation in state economic conditions or state sensitivity to national economic conditions. We find that income volatility is higher in good state times than bad; during good national times, we find volatility is higher in states that are more sensitive to national conditions.